Synthesis and DFT study of novel pyrazole, thiophene, 1,3-thiazole and 1,3,4-thiadiazole derivatives - Fahim, Asmaa Mahmoud; Farag, Ahmad Mahmoud; Shaaban, Mohamed Rabie; Ragab, Eman Ali (European Journal of Chemistry, 2018)
Regioselective facile synthesis of innovative heterocycles from the reaction of 2-cyano-N-cyclohexylacetamide (3) with hydrazonoyl chloride (4) in basic condition afforded amino pyrazole derivative 6. The behavior of acetamide 3 with phenylisothiocyanate in DMF/KOH surveyed by addition of the α-halo ketones to yeild the corresponding thiophene derivative 13a, 13b, 16, 18 and 1,3-thiazoles 21. Reaction of intermediate potassium salt 9 with hydrazonoyl chloride 22a-e furnished the corresponding 1,2,4-thiadiazoles 24a-e. Density functional theory (DFT) calculations at the B3LYP and HF techniques combined with 6-31G(d) basis set to investigate the equilibrium geometry of the innovative compound pyrazoles 6 and the stability affording of HOMO/LUMO molecular orbitals.